Clinical irrelevance of lower titer thyroglobulin autoantibodies in patients with differentiated thyroid carcinoma - Dekker, Bernadette L; van der Horst-Schrivers, Anouk N A; Brouwers, Adrienne H; Shuford, Christopher M; Kema, Ido P; Muller Kobold, Anneke C; Links, Thera P (European thyroid journal, 2022)
Objective Thyroglobulin (Tg) is an established tumor marker for differentiated thyroid carcinoma (DTC) patients. However, Tg immunoassays can be subject to Tg autoantibody (TgAb) interference resulting in incorrect Tg values. Therefore, Tg measurement with liquid chromatography-tandem mass spectrometry (LC-MS/MS) could be promising in patients with TgAbs. In this study, we compared Tg IRMA and Tg-LC-MS/MS analytically in the presence of TgAbs. Furthermore, we compared the clinical interpretation of results obtained by both Tg assays in DTC patients with lower TgAbs titers (<10 U/mL) during 131I ablation therapy. Methods Totally 118 DTC patients diagnosed between 2006 and 2014 in a University Medical Center were followed with the Tg-IRMA (Thermo Fischer Scientific) and ARCHITECT anti-Tg (Abbott Laboratories) assays. We re-analyzed their samples with a sensitive Tg-LC-MS/MS method (Labcorp, limit of quantification of 0.02 ng/mL). Passing-Bablok regression analysis was performed on samples obtained during 131I ablation therapy and follow-up. Results In 304 samples with lower TgAb titers, a good analytical agreement was found between both Tg assays (slope of 1.09 (95% CI: 1.05–1.16)). Fifty-five samples with potentially interfering TgAbs showed higher Tg-LC-MS/MS values than Tg-IRMA (slope of 1.45 (95% CI: 1.12–>>100)). In patients(n  = 91) with lower TgAb titers at the time of 131I ablation therapy, the Tg assays showed a clinical concordance of 91.2, 87.9, and 98.9%, respectively, using a Tg cut-off value of 1.0, 2.0, and 5.0 ng/mL. Conclusions In DTC patients with lower titer TgAbs, Tg-IRMA is still a reliable and useful tumor marker. In DTC patients with potentially interfering TgAbs, Tg-IRMA values decreased due to TgAb interference.